Subduction Zone Geodynamics - Lallemand, Serge. (Springer, 2017)
Subduction is a major process that plays a first-order role in the dynamics of the Earth. This title contains a collection of contributions that were presented in June 2007 in Montpellier (France) in a conference that gave a panorama and discussed the perspectives about 'Subduction Zone Geodynamics'.